ADCP data measured during baited camera lander deployments on the Cabo Verde Abyssal Plain - Danielle de Jonge; Alycia J Smith; Andrew K Sweetman (PANGAEA, 2023)
A total of eight deployments of an autonomous baited camera lander were conducted at the Cabo Verde Abyssal Plain (tropical East Atlantic, Lat. 14.72, Lon. -25.19; Water depth ~4200 m) using either Atlantic mackerel (Scomber scombrus, n=4) or Patagonian squid (Doryteuthis gahi, n=4) bait, to photograph organisms attracted to the bait over roughly 24 hours. The deployments took place during the iMirabilis2 campaign in August 2021 from the research vessel Sarmiento de Gamboa. A deep-sea time lapse camera system with an oblique view of the bait plate and surroundings took a picture every 2.5 min. An ADCP (Aquadopp 6000 m, Nortek) mounted on top of the lander frame took a reading of near bottom currents (~2 meter above bottom) every second. This dataset includes the data downloaded from the ADCP current meter.